Quantitative Evaluation of the Pivot Shift - Relationship to Clinical Pivot Shift Grade: A Prospective International Multicenter Study - Hoshino, Yuichi (Orthop J Sports Med, 2015)
OBJECTIVES: The rotational laxity, or the pivot shift test, is a key to understanding the anterior cruciate ligament (ACL) function after the ACL injury and reconstruction. Various measurement methods have been developed to quantify the pivot shift test, but the clinical implications of the measurement results have not been established mainly because of a wide variability of the pivot shift test between examiners. The purpose of this study was to determine the relationship between quantitative measurement and clinical grade of the pivot shift test at four international centers. METHODS: Seventy-three unilateral ACL injured patients at four different sites were included in this study. While performing the standardized pivot shift test under anesthesia, two quantitative technologies were utilized; an accelerometer and image analysis system using iPad. Accelerometer wireless sensor (KiRA, Orthokey, Italy) was attached on the lateral side of the tibial tubercle using a strap (Figure1A). The tibial acceleration was recorded through a Bluetooth connection to the tablet PC. Image analysis of lateral compartment translation was simultaneously performed using software implemented on iPad (Apple Inc, USA) which tracked the movement of three markers on the lateral side of the knee joint (two on the lateral tibial plateau and one on the lateral femoral epicondyle) to measure the anterior-posterior shift between the lateral tibia and femur (Figure 1B). Tibial acceleration and the lateral compartment translation were compared to the clinical pivot shift grade (grade 0, 1, 2 and 3). Spearman correlations were use to determine the relationship between the quantitative measurements and clinical pivot shift grade. Considering limited number of individuals with a grade 0 and 3 pivot shift test, we used independent t-tests to compare the quantitative measurements between those with a grade 0 or 1 (low grade) pivot shift versus grade 2 or 3 (high grade) pivot shift. The alpha level was set at p<0.05. RESULTS: There were weak correlations between the quantitative measurements and clinical pivot shift grade (acceleration: 0.32, translation: 0.31, p<0.01). High grade pivot shifts had larger acceleration (4.1±1.8 m/sec2) than low grade (3.1±1.8 m/sec2, p<0.05). The difference in tibial translation between high and low grade pivot shifts approached significance (2.4±1.5 vs. 1.7±1.4 mm, p=0.054). CONCLUSION: This study confirms that clinical grading of the pivot shift is subjective and inconsistent. The tools to perform non-invasive, quantitative pivot shift measurements (tibial translation and acceleration) are simple to learn as shown across 4 centers in this study. However, there were only weak correlations between clinical grading and quantitative measurements. From the data of this study, it is suggested to use a simple positive/negative grading and add a quantitative value to it. Future research is needed to determine the correlation of quantitative pivot shift measurements and additional soft tissue injury in patients with ACL injury.